Development of Gadolinium (neutron poison) monitoring system for fuel reprocessing facilities: Computational model and validation with experiments. (August 2018) - Chandrasekaran, S.; Basu, Pew; Krishnan, H.; Sivasubramanian, K.; Baskaran, R.; Venkatraman, B.
Abstract: Gadolinium, a strong neutron absorber is a good choice of material for use as soluble neutron poison for nuclear criticality control in nuclear fuel cycle facilities. During operation, it's availability has to be ensured in order to maintain the sub-critical state of the system. Towards this, periodic monitoring of presence of Gadolinium, a monitoring system was developed. The technique used is based on thermal neutron attenuation characteristics of the medium considered under study. As the design involves, choice of neutron source, moderator assembly and neutron detector sensitivity, Monte Carlo simulation was employed to optimize the design parameters. The details of simulation and experiments carried out to study the feasibility of the method is described. Results of measurements and comparison with computational model developed are also presented in detail. The results indicate that the proposed system can be successfully deployed for remote online monitoring of neutron poison in Fuel Reprocessing.